The Integration of Islamic Educational Values and Local Wisdom in the Novel Inyiak Sang Pejuang by Khairul Jasmi - Fadhila, Liza; M, Iswantir (El-Rusyd, 2026)
The rapid development of globalization and modernization has contributed to the erosion of moral and religious values in society, highlighting the need for educational media capable of integrating Islamic Religious Education with local wisdom. The novel Inyiak Sang Pejuang by Khairul Jasmi represents a literary work that harmoniously combines Islamic teachings with Minangkabau culture through the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah. This study aims to analyze the integration of Islamic Religious Education values and local wisdom contained in the novel as an alternative culture-based learning resource. The study employed a qualitative approach using library research. Primary data were obtained from the novel Inyiak Sang Pejuang, while secondary data were collected from books, scientific journals, and other relevant literature. Data were gathered through documentation techniques and analyzed using content analysis. The findings reveal that the novel integrates the values of aqidah (faith), ibadah (worship), and akhlaq (morality) with Minangkabau local wisdom, including the traditions of surau, deliberation and consensus, mutual cooperation, migration (merantau), and respect for religious scholars and parents. These findings demonstrate that Minangkabau culture is harmonious with Islamic teachings and contributes to strengthening religious character, social values, and cultural identity. Therefore, Inyiak Sang Pejuang is a relevant learning resource for Islamic Religious Education based on local wisdom and character education.